Word stress and meaning stress in the studied language. - G’aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
Pronunciation of one of the syllables or parts of the sentence with a longer (stronger) sound or tone than others is called accent. A stressed sylla ble is a stressed syllable, and the stress usually falls on a vowel. For example: the trees began to sprout.